Is My Stress Out of Place? Bread Wheat Response to Saline Stress Varies in Pattern and Extent Across Experimental Settings - Anne Plessis (Plant Direct, 2025)
ABSTRACT Adopting crops and agricultural practices that help sustain yield under abiotic stress will be a major element of future food security under climate change. However, little of the intensive research into the mechanisms of plant abiotic stress response has translated into improved yield stability. A suspected obstacle to translatability of research findings in this area is artificial experimental conditions, but we lack evidence to support this explanation. Here, we combined a meta‐analysis and an experimental approach to compare the effect of salt stress on wheat yield, growth, and physiology across four distinct experimental settings: field/field‐like conditions, potted plants in a climate chamber, in a greenhouse, and outdoors. The meta‐analysis, comparing responses relative to control conditions over similar ranges of salt stress intensity, confirmed that field conditions led to more limited impact on yield than in the other three experimental settings and uncovered differences in how shoot and root biomass are relatively affected by salt stress between greenhouse and outdoors pot experiments. In our experiment, we identified very distinct responses for each of the four experimental settings, with plants outdoors accumulating more Na+ and proline than plants indoors, and shoot growth and yield were least affected by stress in field‐like conditions and most affected in the climate chambers. Together, these results suggest that the nature of the acclimation mechanisms used by wheat to face salt stress can depend on the experimental setting. While our findings need confirmation for other crops and abiotic stresses, we recommend renewed attention to the conditions under which experiments are carried out and to favor more realistic growth conditions when possible.